INTERNATIONAL SEMINAR OF ENTREPRENEURSHIP - Andi Adawiah; Asmini Asmini; Andi Nurul Aksa; Asmi Rahayu; Andi Zulkifli Nusri; A. Muh. Yusuf (Adisam Publisher, 2025)
This conference presents the findings of international seminar about entrepreneurship in digital era held in 2024. The main focus of the study is entrepreneurship in digital era thrives on innovation. The research examines the role of digital platforms, social media, and artificial intelligence in supporting the growth of small and medium enterprises (SMEs). The result highlight that digital entrepreneurship requires not only technological innovation but also strong managerial skills and digital literacy. The article offers strategic recommendations for entrepreneurs and policymakers to build more adaptive and sustainable business ecosystem.